THE PROBLEM OF PSYCHOSEXUAL THEORY: A COMPARATIVE ANALYSIS OF SIGMUND FREUD AND ABDULLAH NASHIH 'ULWAN - Arroisi, Jarman; Kholid, Husna Hisaba (IAIN Kendari, 2024)
Freud's psychosexual is a theory that is quite influential in describing human personality in the contemporary era. Freud viewed that human mental health disorders (neurotic) were greatly influenced by his sexual experiences in childhood. In contrast to Islam, Abdullah Nashih 'Ulwan through his work describes a more holistic concept of child development that includes various aspects of human qualities. Therefore, this paper aims to conduct a comparative study between Abdullah Nashih 'Ulwan's concept of child development and Freud's Psychosexual. This research is a library research and the data sources used consist of primary data sources of Sigmund Freud's works and secondary data sources in the form of books, which are relevant to this research to strengthen the argumentation and to complement the data from the research results. The data analysis technique used by the author in this research is content analysis. As for the findings that the author gets from this paper, first, psychosexuality has epistemological problems and worldviews that are not in accordance with the Islamic worldview. second, psychosexuality views human nature partially, which only sees from the aspect of sexuality alone. Third, 'Ulwan describes a more holistic child development by reviewing all aspects of human quality itself which includes aspects of Īmāniyyah, khuluqiyyah, Ijtimā'iyyah, a'qliyyah, nafsiyyah, ruhiyyah and Jinsiyyah.